Analysis of Nitroxide‐Based Distance Measurements in Cell Extracts and in Cells by Pulsed ESR Spectroscopy. Issue 12 (2nd May 2017) - Lawless, Matthew J.; Shimshi, Amit; Cunningham, Timothy F.; Kinde, Monica N.; Tang, Pei; Saxena, Sunil
Abstract: Measurements of distances in cells by pulsed ESR spectroscopy afford tremendous opportunities to study proteins in native environments that are irreproducible in vitro. However, the in‐cell environment is harsh towards the typical nitroxide radicals used in double electron–electron resonance (DEER) experiments. A systematic examination is performed on the loss of the DEER signal, including contributions from nitroxide decay and nitroxide side‐chain cleavage. In addition, the possibility of extending the lifetime of the nitroxide radical by use of an oxidizing agent is investigated. Using this oxidizing agent, DEER distance measurements are performed on doubly nitroxide‐labeled GB1, the immunoglobulin‐binding domain of protein G, at varying incubation times in the cellular environment. It is found that, by comparison of the loss of DEER signal to the loss of the CW spectrum, cleavage of the nitroxide side chain contributes to the loss of DEER signal, which is significantly greater in cells than in cell extracts. Finally, local spin concentrations are monitored at varying incubation times to show the time required for molecular diffusion of a small globular protein within the cellular milieu. Abstract : Made to measure : In‐cell pulsed ESR spectroscopy reveals that cleavage of the nitroxide probe side chain contributes to a loss in signal for distance measurements. In addition, the use of an oxidant extends the lifetime of the nitroxide radical, increasing the possible incubation times by 50 %. Finally, local spin concentrations are compared, revealing the time necessary for the labeled protein to equilibrate in the cellular environment.